Morpho-diversity of Oryza Sativa L. genetic cultivars from West Bengal, India - Saha, Partha Sarathi; Paul, Subhabrata; Ghosh, Biswajit (International Journal of Bio-resource and Stress Management, 2023)
Partha Sarathi Saha, Subhabrata Paul and Biswajit Ghosh* Plant Biotechnology Laboratory, Department of Botany, Ramakrishna Mission Vivekananda Centenary College, Rahara, Kolkata, West Bengal (700 118), India The present study was undertaken for germplasm collection, and morphological characterization of fifty Oryza sativa L. cultivars from West Bengal, India. The starch-iodine test shows that the Borapaddy variety is very sticky, indicating relatively higher amylopectin content. A positive correlation (p= 0.05; two-tailed) was observed between the number of rice grains per panicle and the leaf length or leaf width, suggesting that leaf surface area is intimately linked to photosynthetic capabilities and food storage in the grains of each panicle. The odour perceived after alkaline treatment of grains, revealed that the Tulaipanji, Tulshi bhog, Bhog dhan, Khas dhan, Chini atap, Kalojire, Phulpakri, Kalanunia, Prasad bhog, Kalojoha, Katari bhog, Badsha bhog and Danaguri varieties were aromatic. The results underscore a need for conservation strategies that optimize use of rare cultivars in breeding programs.